Respuestas
Respuesta dada por:
2
Aplicamos propiedades:
![x(x + 1)(x + 2) = x + (x + 1) + (x + 2) \\ x( {x}^{2} + 2x + x + 2) = 3x + 3 \\ {x}^{3} + 3 {x}^{2} + 2x - 3x - 3 = 0 \\ {x}^{3} + 3 {x}^{2} - x - 3 = 0 \\ x( {x}^{2} - 1) + 3( {x}^{2} - 1) = 0 \\ ( {x}^{2} - 1)(x + 3) = 0 \\ x =1 \\ x = - 1 \\ x = - 3 x(x + 1)(x + 2) = x + (x + 1) + (x + 2) \\ x( {x}^{2} + 2x + x + 2) = 3x + 3 \\ {x}^{3} + 3 {x}^{2} + 2x - 3x - 3 = 0 \\ {x}^{3} + 3 {x}^{2} - x - 3 = 0 \\ x( {x}^{2} - 1) + 3( {x}^{2} - 1) = 0 \\ ( {x}^{2} - 1)(x + 3) = 0 \\ x =1 \\ x = - 1 \\ x = - 3](https://tex.z-dn.net/?f=x%28x+%2B+1%29%28x+%2B+2%29+%3D+x+%2B+%28x+%2B+1%29+%2B+%28x+%2B+2%29+%5C%5C+x%28+%7Bx%7D%5E%7B2%7D++%2B+2x+%2B+x+%2B+2%29+%3D+3x+%2B+3+%5C%5C++%7Bx%7D%5E%7B3%7D++%2B+3+%7Bx%7D%5E%7B2%7D++%2B+2x+-+3x+-+3+%3D+0+%5C%5C++%7Bx%7D%5E%7B3%7D++%2B+3+%7Bx%7D%5E%7B2%7D++-+x+-+3+%3D+0+%5C%5C+x%28+%7Bx%7D%5E%7B2%7D++-+1%29+%2B+3%28+%7Bx%7D%5E%7B2%7D++-+1%29+%3D+0+%5C%5C+%28+%7Bx%7D%5E%7B2%7D++-+1%29%28x+%2B+3%29+%3D+0+%5C%5C+x+%3D1++%5C%5C+x+%3D++-+1+%5C%5C+x+%3D++-+3)
Nos quedan esos 3 valores que cumplen con la ecuación.
Nos quedan esos 3 valores que cumplen con la ecuación.
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años